ANALYSIS OF ANXIETY AND FAMILY SUPPORT WITH CANCER-RELATED FATIGUE AMONG CANCER PATIENTS UNDERGOING RADIOTHERAPY - Giyaningtyas, Ika Juita; Estiadewi, Primalova Septiavy (Jurnal Mitra Kesehatan, 2026)
Introduction: Cancer-Related Fatigue is the most common and debilitating symptom experienced by cancer patients, significantly reducing their quality of life. Psychological factors such as anxiety and family support are thought to contribute to the development of CRF; however, empirical evidence remains limited, particularly among patients undergoing radiotherapy. This study aimed to analyze the relationship between anxiety and family support with cancer-related fatigue among patients receiving radiotherapy. Methods: This quantitative study employed a cross-sectional design conducted at the Radiotherapy Center of X Hospital, Bekasi, in July 2025. Samples were selected using consecutive sampling. The inclusion criteria were cancer patients currently undergoing radiotherapy, while patients with cognitive  impairments were excluded. Data were collected using the State-Trait Anxiety Inventory (STAI) to measure anxiety, a family support questionnaire, and the Brief Fatigue Inventory (BFI) to assess cancer-related fatigue. Data were analyzed using Spearman’s rho correlation test. Results: A total of 34 respondents participated, with a mean age of 48.18 years. The majority were female (88.2) and had been diagnosed with cancer for than 1 year (61.8). Most participants experienced moderate anxiety (55.9), good family support (76.5), and mild fatigue (97.1). The analysis showed no significant correlation between anxiety and CRF (p = 0.092; r = –0.293) or between family support and CRF (p = 0.267; r = –0.196). Conclusion: There was no significant relationship between anxiety and family support with cancer-related fatigue among cancer patients undergoing radiotherapy. Other factors such as physiological condition, cancer stage, nutritional status, and individual coping mechanisms may have a greater influence on patients’ fatigue levels.